STUDY OF BIOPHILIC CONCEPT IN NG TENG FONG GENERAL HOSPITAL SINGAPORE - Izzat Fadhlur Rahman; Finta Lissimia (Ide dan Dialog Desain Indonesia (Idealog), 2022)
A hospital is a medical facility that aims to improve the quality of life of the community through the process of preventing, treating, and treating health problems. Hope of recovery and the risk of death come together, creates the impression of the hospital as a tensed up place so that it af ects the psychological condition of the patient and cause other problems. Biophilic is an architectural approach that aims to have a positive influence on the human psyche by meeting the needs of its instinct to be af iliated with nature. This research aims to understand the application of the biophilic concept at Pondok Indah Bintaro Hospital. The method used is descriptive qualitative with analysis based on the theory of 14 biophilic patterns by Browning, W.D., Ryan, C.O., and Clancy, J.O. Hospitals with biopihlic architecture represent natural systems at the scale of site through relationships with biotic and abiotic components (nature in space). On the building scale, biophilic is applied through architectural details that analogize natural forms (nature analogues), as well as spatial characteristics of nature that influence human perception (nature of space). Ng Teng Fong Hospital applies 12 of the total 14 biophilic patterns, or with a percentage of 86%. Patterns that are not applied are presence of water and connection with natural system. Keywords : Biophilic, hospital, human health, nature